TIME IN THERAPEUTIC RANGE (TTR) IN ATRIAL FIBRILLATION WITH WARFARIN THERAPY IN SEMARANG, INDONESIA - Della Dafina Sekarsari; Pipin Ardhianto; Erwin Kresnoadi; Mochamad Ali Sobirin (Jurnal Kedokteran Diponegoro)
Background: Atrial fibrillation is one of the factors forming thromboembolism. The thromboembolism can be prevented with warfarin. A side effect of warfarin is increasing the occurrence of bleeding, these therapy requires an evaluation of its usage. These evaluations can be seen in the Time in Therapeutic Range (TTR) patients. TTR is the duration in which the International Normalized Ratio (INR) patients in referral value are 2.0-3.0. TTR > 70% can prevent bleeding on FA patients with warfarin therapy.